2019
DOI: 10.24310/innoeduca.2019.v5i1.5175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del uso de las TIC en estudiantes de la Universidad de Málaga: diferencias de género

Abstract: Con la implantación del Espacio Europeo de Educación Superior (EEES), una de las cuestiones más relevantes que se incluyen en la formación universitaria es el manejo de las nuevas Tecnologías de la  Información y la Comunicación (TIC) por parte del alumnado. En esta investigación  se ha evaluado el uso de las TIC en 79 estudiantes (Medad=20,43, DT=3,83) de primer curso de Pedagogía de la Universidad de Málaga, y se han analizado las diferencias de género en el ámbito tecnológico. Para la recogida de datos se u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In this sense, the men were more inclined towards the development of digital methodologies and systems of evaluation, in contrast to the studies by [18,41], who indicated that women were more prone towards this. As a result, hypothesis 1 must be rejected (The women use the digital tools more as compared to the men), just as the results from the study by [26,27,[43][44][45][46][47], and in contrast to the results found by [26,29,48,49] whose research determined this aspect as a possible creator of a gender digital divide [50]. In this sense, it should be indicated that the academic community does not seem to have reached a consensus about the variable gender, as shown by different studies conducted about the topic [26,29,[44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the men were more inclined towards the development of digital methodologies and systems of evaluation, in contrast to the studies by [18,41], who indicated that women were more prone towards this. As a result, hypothesis 1 must be rejected (The women use the digital tools more as compared to the men), just as the results from the study by [26,27,[43][44][45][46][47], and in contrast to the results found by [26,29,48,49] whose research determined this aspect as a possible creator of a gender digital divide [50]. In this sense, it should be indicated that the academic community does not seem to have reached a consensus about the variable gender, as shown by different studies conducted about the topic [26,29,[44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Today's students are portrayed by the media as "digital natives" (Creighton, 2018). This new generation of students is defined as emotionally attached users of ICT (Turner, 2015), mainly for leisure purposes (Allaby, 2018;Aranda et al, 2019). However, this perspective was lately criticised by different researchers (Flynn, 2021;Kirschner & van Merriënboer, 2013), as perhaps their competence levels are not focused on educational technology (Judd, 2018).…”
Section: The Digital Competence Of Studentsmentioning
confidence: 99%
“…The effect of the digital gap on social exclusion (Gómez-Trigueros et al, 2023 ), as well as the influence of the gender digital gap as the second digital gap (Garrido et al, 2019 ), is an additional barrier to overcome for the comprehensive development of citizenship in the twenty-first century (Joiner et al, 2015 ). As stated by Mariscal et al ( 2019 ), "there is still a stark and pervasive gender inequality in terms of access, ownership of digital devices, digital fluency as well as the capacity to make meaningful use of the access to technology".…”
Section: Introductionmentioning
confidence: 99%
“…Lo cual, se corrobora parcialmente con estudios como el de Torres-Coronas y Vidal-Blasco (2015), quienes encontraron que los hombres se destacan en la comunicación en línea, pero en cambio las mujeres lo hacen en el manejo de redes sociales. Así mismo, Aranda et al (2019) señala que, si bien no hay diferencias por sexo en los conocimientos básicos y medios de las TIC, sí se presentan diferencias cuando se necesitan conocimientos más complejos para su manejo. Estas diferencias podrían deberse al número y especialidad de los estudiantes encuestados, y al énfasis de cada instrumento de obtención de datos en unos u otros usos de las TIC.…”
Section: Discusión Y Conclusionesunclassified